PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK DENGAN STRATEGI REACT - Hilma Yunis (Departemen Matematika, 2020)
This paper discusses the mathematical problem solving abilities of students that can be improved with the REACT strategy. The low ability of students to solve mathematical problems is due to the learning process that is not optimal. Through this research, it describes theoretically how the REACT strategy can improve students' mathematical problem solving abilities.This research type is literature study. Data collection is done by searching, collecting and analyzing sources related to topics discussed either from textbooks, journals or other sources. The data analysis used was content analysis. This analysis is needed to discuss in depth the improvement of students' mathematical problem solving abilities with the REACT strategy.The conclusion of this literature study is that theoretically the students' mathematical problem solving abilities can be improved with the REACT strategy. The application of each stage of the REACT strategy can optimize the learning process so that it can help students to improve their mathematical problem solving abilities. The stages of relating will encourage students to be able to understand the problem by relating a problem to the knowledge they have independently. In the experiencing stage, students will be guided to construct their knowledge independently through exploration and discovery activities. The applying stage will encourage students to be able to apply the concept to realistic and relevant practice questions. At the cooperating stage, students will be encouraged to be active in solving problems correctly, completely and systematically in groups. At the transferring stage, students are guided to transfer the knowledge they have acquired into other contexts to be able to solve more complex problems. Keywords – Mathematical Problem Solving Abilities, REACT Strategy